Players and Purists: Networking Strategies and Agency of Service Professionals - Bensaou, Ben; Galunic, Charles; Jonczyk Sédès, Claudia (My University, 2014)
Social capital research has established the performance advantages of networking. However, we know surprisingly little about the strategies individuals employ when networking and, in particular, the underlying agency mechanisms involved. Network analysis tends to presume structural determinism and ignore issues of endogeneity rather than explore how actors draw on schemas, beliefs, and values in developing their networks. This empirical paper induces three networking strategies of newly promoted service professionals operating within two firms (AuditCo and ConsultCo) over a 16-month period. Using a grounded theory building approach, we first establish a set of core categories that capture networking behavior. We then conduct a cluster analysis revealing three distinct networking configurations or strategies: Devoted Players, Purists, and Selective Players. We also reveal the distinct agency involved in each profile and investigate the extent to which these networking strategies correlate with variables that shed light on issues of endogeneity and deepen our understanding of the strategies (including network structure and socialization progress in the players’ new jobs).
Keywords: Networking; Management; strategy